Antecedents and consequences of employee well-being: empirical study on Saudi Aramco - Alghamdi, Mansour; Ng, Siew Imm; Ho, Jo Ann; Abdulsamad Ali, AKRAM; Ramachandran, Sridar (Society for Science and Education, 2021)
This study addresses how employee well-being and knowledge sharing behavior can be managed within challenging work factors in the workplace environment. Besides identifying antecedents to well-being, it also seeks to examine the impact of well-being (psychological, physical, and social) on knowledge sharing behavior (tacit and explicit). The methodology of research in the present study is quantitative. The survey technique was used in data collection, it was conducted among 362 Saudi Aramco employees using the judgmental sampling method. Smart PLS was used for analyzing data. The findings illustrated that 1. Job hazards were found to affect the physical well-being of employees significantly. 2. As a result of improvement in physical and social well-being, better knowledge-sharing behavior in both tacit and explicit dimensions was demonstrated. In specific, tacit knowledge-sharing behavior is motivated more by physical well-being while explicit knowledge-sharing behavior is by social well-being. 3. Workplace conflict is found positively related to social well-being, contradicting hypothesized relationship. This seems to indicate Saudi Aramco employees embrace differences in view, beliefs, and feelings at work, and open discussion of conflicts enhances their social well-being. This study provides ideas to human resource management on strategies to enhance employee well-being for improved knowledge sharing behavior. Also, managers are encouraged to use open debates of differing views to resolve work matters professionally. This study deviates from current employee well-being studies by recognizing three different types of employees well beings (psychological, physical, and social) that contribute differently to knowledge sharing behavior. Also, it identifies factors that determine employee well beings.